IMPROVING WRITING ABILITY FOR STUDENTS - tris - Trismanto (LINGUAMEDIA Journal, 2022)
Everyone basically has the ability to communicate, especially writing. The ability to write is acquired through a learning process not inherited. In college, the ability to write is very important for students, especially for compiling scientific works such as papers, theses, theses, dissertations, and reports. Problems faced by novice writers. These include: (1) fear of starting, (2) not knowing when to start, (3) organizing, and (4) language. Determining the initial attitude for novice writers will determine success or failure in writing. Regarding the process approach, writing activities are divided into three stages, namely: pre-writing stage, writing stage, and post-writing stage. Keywords: communicating, pre-writing, writing process, post-writing.